Psychometric properties of an instrument of reasons for admission to university careers in health sciences - Juan. F. Caldera Montes; O.U. Reynoso González; Y. Sughey González Torres; M.R. Zamora Betancourt (Universitat Politècnica de València, 2018)
The  purpose  of  this  research  was  to analyze the validity and reliability of the instrument called "Reasons for Admission to Careers in Health Sciences (MICCS) (acronym  in  Spanish)".  The  study  was developed  with  a  non-probabilistic  and incidental sample of 194 students from a higher education institution in the state of  Jalisco,  Mexico.  After  reviewing  the contenty  validity  by  expert  judges,  an exploratory factor analysis was executed (principal components method and Varimax rotation). Seven dimensions were defined under the critery of theoretical position and inflection of the curve of sedimentation. The indexes of KMO (0.788) and Bartlett (X (990) = 2916.36, p=0.000) reported an appropriate model. Items with theoretical inconsistencies and saturations under of 0.4 were eliminated. Its internal consistency was acceptable (α=0.834). The final version of the instrument consisted of 30 items and six independent factors, showing   satisfactory   psychometric properties.  Finally  were  contrasted  the reasons for entering careers in medicine, nursing,  nutrition  and  dentistry  to  the variables of sex, vocational orientation and type of school. It is proposed to extend the investigation of reasons for entering science careers health by using the scale in public and private institutions of higher education; In addition, it is recommended to analyze the relationship of the reasons for admission and psychosocial variables such  as  academic  performance,  lag, desertion, satisfaction and academic stress.